Research and methodological approach to scoring the impact of banks performing operations involving transnational capital on the banking system of Ukraine - Tkachenko, Nataliia; Momot, Oleksandr (Herald of Economics, 2019)
The article examines the impact of banks performing operations involving transnational banking capital on the banking system of Ukraine through the use of the principal components analysis. This approach is related to the method of multidimensional statistical analysis and is widely used to reduce the dimension of an analyzed set of attributes, and to select the most informative indicators and classification features.From the research, it is found that the principal components analysis is based on the idea according to which structural properties of relations between variables can be determined by their dependence on fewer non-measureable (concealed, latent, hypothetical) general factors.The direct estimation of the impact of banks performing operations involving transnational capital on the banking system of Ukraine is carried out by means of the application package named Statistica. For this analysis, the following relative indicators showing how Ukraine’s banks perform operations involving transnational capital are used: 1) percentage of funds raised from legal entities; 2) percentage of funds raised from individuals; 3) percentage of owned capital; 4) percentage of profit / loss after tax; 5) percentage of assets; 6) percentage of loans and debts of legal entities; 7) percentage of loans and debts of individuals.Based on the research findings, it is shown that there are three principal components which take into account more than 5% of total variance. However, there is only one component among them the value of which exceeds 1. The second component equals 0.954179, meaning that it approaches 1. The scree plot shows that the breaking point can be viewed as the eigen-value of correlation matrix which equals 23.85%. Consequently, the two principal factors have an essential impact on the processes of foreign capital penetration into Ukraine.It is claimed that the expansion of transnational banking capital into the banking system of Ukraine is controversial. On the one hand, these trends are quite obvious. On the  other hand, financial, economic, military, and political instability hampers such processes. In conclusion, it should be stressed that unlike other approaches, the research and methodological approach to scoring the impact of banks performing operations involving transnational capital on the banking system of Ukraine, is based on the principal components analysis. This makes it possible to develop an aggregate index which characterizes the impact of banks performing operations involving transnational capital on the banking system of Ukraine, and to use it for monitoring of structural changes in the banking system.